2017
DOI: 10.1007/s13317-017-0101-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D deficiency in systemic lupus erythematosus incidence and aggravation

Abstract: Vitamin D is one of the main groups of sterols; playing an important role in phospho-calcic metabolism. The conversion of 7-dehydrocholesterol to pre- vitamin D3 in the skin, through solar ultraviolet B radiation, is the main source of vitamin D. Since lupus patients are usually photosensitive, the risk of developing vitamin D deficiency in is high in this population. Although evidences showed the connotation between systemic lupus erythematosus (SLE) and vitamin D through which SLE can lead to lower vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 88 publications
(115 reference statements)
2
38
0
3
Order By: Relevance
“…Damage caused by antigen binding (ds-DNA and ANA) with antibodies will cause activation and recruitment of various immune responses by releasing various pro-inflammatory mediators, such as TNFα and IL-1β. Subsequent pro-inflammatory mediators will cause more massive damage due to immunogenic inhibitory activity [21], [22], [20]. Vitamin D is a regulator that plays a role in maintaining the body's defense system homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Damage caused by antigen binding (ds-DNA and ANA) with antibodies will cause activation and recruitment of various immune responses by releasing various pro-inflammatory mediators, such as TNFα and IL-1β. Subsequent pro-inflammatory mediators will cause more massive damage due to immunogenic inhibitory activity [21], [22], [20]. Vitamin D is a regulator that plays a role in maintaining the body's defense system homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, vitamin D supplementation seems to ameliorate inflammatory and haemostatic markers and can improve clinical course. 33 SLE has an impact on many aspects of patients' health, so a multidisciplinary team including the GP , rheumatologist and other specialists must co-operate to optimise the follow-up of SLE patients. 9…”
Section: The Gp's Role In Managementmentioning
confidence: 99%
“…Indeed, the available evidences have introduced Vitamin D as an immune modulator for the immune system. [7] Previous reports showed that Vitamin D deficiency/insufficiency was high in SLE patients. The promising results reported for Vitamin D administration in several animal models suffered from inflammatory bowel disease,[8] autoimmune thyroiditis,[9] Type I diabetes mellitus,[10] and SLE.…”
Section: Introductionmentioning
confidence: 99%